GE_GERICHTE A/2470/2016 vom 13. Oktober 2016 - GE Cour de justice (2016)
SEQUES; CADUCI; NOTCOM; FORSEQ; RESDEL; CONPOU; SUCCES; VALSEQ; DECES | LP.33.4; LP.38.2; LP.49; LP.59.1; LP.279.1; LP.279.3; LP.280.1